IMPLICATION OF LANGUAGE ATTITUDE TO THE LINGUISTIC COMPETENCE OF STUDENTS IN SYNCHRONOUS CLASSES - ARIANE NEL SEDANO (Journal of English Education and Linguistics, 2022)
Verbal Communication is considered a performance of language. This means that what may have been spoken may also imply a representation of ideologies, constructed realities, and an imitation of life. Language reconnoiters the speaker’s background and points toward the holistic overview of what is seen and felt in real socio-cultural engagements. Through the performance of language, the behavior of it is observed and may imply the proficiency of the student’s fluency in the verbal ability. With this, the researcher conducted an assessment of this linguistic performance in the classroom set-up during the synchronous class to determine the existing language attitude and problematize its sociolinguistic implication of it so that certain measures may be raised to improve the current classroom language management. This is anchored on Noam’s Chomsky’s Theory on Linguistic Performance which is referred to the production and comprehension of language use. Also, the Theory on the Language Attitude by Thomas Hatherley Pear in which he mentioned that sufficient cues for the speaker’s personality are reflected in the assessed linguistic voice used in language. This study conducted is a qualitative study that involved class observation, recording, transcription, analysis, and interpretation in a college English class at the Camarines Sur Polytechnic Colleges. The findings of the study concluded that the attitude of students in English language use involves code-switching and -mixing, language fillers, literacy in technology use, language misuse, and language variety. This identified language attitude implies Linguistic Turn in Academic Conversation and Expressive Language is Linguistic Competence.